2016
DOI: 10.2196/jmir.5502
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Traditional Newspaper Advertisement: Leveraging Facebook-Targeted Advertisement to Recruit Long-Term Smokers for Research

Abstract: BackgroundSmokers are a stigmatized population, but an important population to reach for the purpose of research. Therefore, innovative recruitment methods are needed that are both cost-effective and efficacious in recruiting this population.ObjectiveThe aim of the present article was to evaluate the feasibility of Facebook-targeted advertisement to recruit long-term smokers eligible for lung cancer screening for a descriptive, cross-sectional survey.MethodsA social media recruitment campaign was launched usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
93
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 27 publications
9
93
1
1
Order By: Relevance
“…In further sections of this paper, the article by Head et al [35] is counted as a single article or 2 articles, according to whether the conclusions from the 2 studies pertinent to the outcomes of this paper are the same or different. Out of 30 studies, 12 studies (40%) reported higher rates of recruitment through social media as compared with any of the other methods used [14-17,26,28,31,32,35, 36,41,42] and 15 studies (50%) reported recruitment via social media to be less effective than at least one other method used [18-21,23-25, 27,33-35,37-40]. Heffner et al [20] and Rabin et al [24] found social media to be the least effective method out of multiple (>2) recruitment methods used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In further sections of this paper, the article by Head et al [35] is counted as a single article or 2 articles, according to whether the conclusions from the 2 studies pertinent to the outcomes of this paper are the same or different. Out of 30 studies, 12 studies (40%) reported higher rates of recruitment through social media as compared with any of the other methods used [14-17,26,28,31,32,35, 36,41,42] and 15 studies (50%) reported recruitment via social media to be less effective than at least one other method used [18-21,23-25, 27,33-35,37-40]. Heffner et al [20] and Rabin et al [24] found social media to be the least effective method out of multiple (>2) recruitment methods used.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 studies that found social media to be the best method of recruitment, 8 were observational studies [14,16,17,26,28,31,35,41] and the remaining 4 were interventional studies [15,32,36,42], as shown in Multimedia Appendix 2. In addition, 6 of these studies targeted populations deemed hard to reach [16,17,28,31,32,36], and 6 studies targeted specific conditions or disorders [14,16,17,28,31,32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, Facebook also offers more sophisticated targeting options, based on "interests" (for example, "healthy eating" and "bodybuilding"); Facebook gleans this information from information users provide about themselves, such as Facebook pages they like or Facebook groups they join [8]. In other publications about Facebook advertising, "interests" have also been referred to as "keywords" [9][10][11] and "key profile words" [12]. However, as Pedersen and Kurz [13] note, recruiting based on Facebook interests or "likes" will fail to capture many populations.…”
Section: Designing the Advertising Campaignmentioning
confidence: 99%